Implementation of A Digital Based Accounting System for Village Owned Enterprises (BUMDES) West Kaduagung Village - Afridayani; Pramono, Nugroho Heri; Kambut, Anasril (Indonesian Journal of Devotion and Empowerment, 2025)
This community service aims to increase the financial management capacity of West Kaduagung Village Village-Owned Enterprises (BUMDes) through the implementation of a digital-based accounting system. This program overcomes obstacles such as manual recording, potential reporting errors, and lack of transparency. Activities include outreach, intensive training, system implementation, and post-implementation assistance. The results show a significant increase in the understanding and skills of BUMDes administrators regarding basic accounting and the use of digital systems. This system increases transparency, efficiency and accountability in financial management, supports the creation of fast and accurate financial reports, and makes strategic decision making easier. Challenges such as limited technological infrastructure and initial resistance from administrators were overcome through a participatory approach. This program has a positive impact on village fund management and has the potential to become a model for other BUMDes. Recommendations include improving technology infrastructure, expanding training, and collaborating with educational institutions and technology providers. The continuation of the program is expected to strengthen the role of BUMDes in competitive and inclusive village economic development.